BIOLOGY AND FISHERY OF THE PALK-BAY SQUID, SEPIOTEUTHIS ARCTIPINNIS GOULD - Rao, K Virabhadra (Indian Journal of Fisheries, 2016)
The only account of the *Palk-Bay Squid, which supports an ancient and locally well-known minor industry in the Ramnad District of the Madras State is that of Hornell (1917, 1922) who has described it as ’Loligo sp.’ The wide long fins extending almost the whole length of the mantle, as shown in his figures, indicate that the form dealt with is a member of the genus Sepioteuthis and not of Loligo.